Leadership and student outcomes: a case study of a high-performing and a low-performing secondary school in Klang Valley, Malaysia - Chay, Josephine Choy Mee (2021)
This dual-case study Malaysian research explores leadership and student outcomes in two contrasting schools in an affluent neighbourhood within Klang Valley, a highly populous and developed urban area close to the capital, Kuala Lumpur. The schools were purposively chosen because their external environments are similar. The main difference between the two schools is their student performance. School 1 is a high performing school, and has less than 5% of low SES students, while school 2, a low performing school, has more than 20% of low SES students. Using a mixed-methods approach, the schools’ performance was analysed through documentary analysis, school leaders’ interviews, teachers’ surveys, and classroom observations. The research findings yield some important considerations for policy and practice. While an instructional leadership style, and an emphasis on academic press, promote enhanced student outcomes, maintaining academic excellence requires a team effort. Firstly, the practice of frequent rotation of principals, as seen in School 2, may not be yielding positive long-term effects, especially for low-performing schools. This study shows that a longer principal tenure is crucial for sustained improvement in academic performance. Secondly, principals should ensure succession planning or internal promotion is put in place for senior leadership positions in the school. While there may be a fear of entrenching a negative culture that is resistant to change, this could be easily mitigated by monitoring the school’s performance. Thirdly, building a positive culture that is conducive to teaching and learning, helps to sustain the momentum of change in an improving or transformed school.